Effect of Centella asiatica Extract on Anti-obesity Suppression via Inhibition of Adipogenesis-related Gene Expression in Preadipocyte - HONG, Ji Woo; PARK, Ha Young; KIM, Han A; KIM, Jin Woo (Food Science and Technology, 2023)
The present study was conducted to investigate the anti-oxidant and anti-obesity activities of Centella asiatica hot-water extract (CHE). Total polyphenol content and radical scavenging activity were evaluated for the anti-oxidant activity of CHE, and 14.4 mg GAE/g DM and 82.6% were measured, respectively. Lipase activity inhibition, an anti-obesity marker, was measured as 68.1%, confirming that triglyceride hydrolysis was significantly inhibited by CHE. To study the anti-obesity mechanism, mRNA expressions of peroxisome proliferator activated receptor-γ (PPAR-γ), CCAAT enhancer binding protein-α (CEBP-α), fatty acid synthase (FAS), and stearoyl-CoA desaturase1 (SCD1) in 3T3-L1 were evaluated. The level of mRNA expression was significantly suppressed by 1.52, 1.81, 1.13, and 1.18 times, respectively, compared to the control group, confirming that CHE had an anti-obesity effect by inhibiting adipocytes development and lipid accumulation. These results indicate that CHE can be used as a raw material for functional foods and pharmaceuticals with anti-oxidant and anti-obesity potential by reducing lipase activity and preadipocyte differentiation.